2009
DOI: 10.2119/molmed.2009.00118
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Expression of Insulin Signaling Pathway Molecules in Endometria from Polycystic Ovary Syndrome Women with or without Hyperinsulinemia

Abstract: Polycystic ovary syndrome (PCOS) is an endocrine-metabolic disorder associated with insulin resistance and compensatory hyperinsulinemia. Scarce information is available on the expression of molecules involved in the insulin pathway in endometria from women with PCOS. Therefore, we examined the protein levels of insulin-signaling molecules, like insulin receptor, insulin-receptor substrate (IRS)-1, pIRS-1Y612, Akt, AS160, pAS160T642 and GLUT4 in endometria from PCOS women with or without hyperinsulinemia. Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 45 publications
1
65
1
Order By: Relevance
“…The lower mRNA levels of IGFRI and InsR in the present study was similar to what occurred in opposite conditions of proliferative phase endometria of women with PCOS (29). It has been postulated that, in patients with PCOS, hyperinsulinemia would cause insulin binding to IGFRI, in addition to InsR, and this would be responsible for cell proliferation and its outcomes, endometrial hyperplasia, and carcinoma.…”
Section: Discussionsupporting
confidence: 88%
“…The lower mRNA levels of IGFRI and InsR in the present study was similar to what occurred in opposite conditions of proliferative phase endometria of women with PCOS (29). It has been postulated that, in patients with PCOS, hyperinsulinemia would cause insulin binding to IGFRI, in addition to InsR, and this would be responsible for cell proliferation and its outcomes, endometrial hyperplasia, and carcinoma.…”
Section: Discussionsupporting
confidence: 88%
“…However, whether the reduction of GLUT4 expression is related to endometrial cell function remains unclear. Fornes et al [26] recently investigated insulin receptor substrates IRS-1-and AS160-related protein expression in the endometrium and found that IRS-1 and AS160 expression was decreased in patients with PCOS and hyperinsulinemia, which led to a reduction of the expression and translocation capacity of GLUT4, affecting endometrial glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…However, several groups have presented evidence that SLC2A4 expression is decreased in endometrial biopsies from women with PCOS versus control (Mozzanega et al . 2004, Fornes et al . 2010, Kohan et al .…”
Section: Pcos and Gluts In The Endometriummentioning
confidence: 99%